An Extended, Trust-Wide Audit Assessing the Handover Process Between Mental Health Inpatient Services and Emergency Departments - Rebecca Joy; Rachael Elliott; Seonaid Beaumont; Femi Osukoya; Sumayyah Khan (BJPsych Open)
Aims: A primary audit revealed widespread non-compliance with NICE Quality Standard (QS174) in patient handovers between the emergency department and a psychiatry inpatient unit. This second audit evaluated whether the issue was specific to one ward and/or emergency department or if it was prevalent across the trust.